2011
DOI: 10.11591/ijece.v1i2.86
|View full text |Cite
|
Sign up to set email alerts
|

A Survey Report On Elliptic Curve Cryptography

Abstract: A digital predistortion (DPD) technique based on an iterative adaptation structure is proposed for linearizing power amplifiers (PAs). To obtain proper DPD parameters, a feedback path that converts the PA's output to a baseband signal is required, and memory is also needed to store the baseband feedback signals. DPD parameters are usually found by an adaptive algorithm by using the transmitted signals and the corresponding feedback signals. However, for the adaptive algorithm to converge to a reliable solution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 16 publications
(1 reference statement)
0
4
0
Order By: Relevance
“…They claim that the Montgomery Ladder-based ECSMA saves 50% space and 45% time, driven by the Karatsuba multiplier's sub-quadratic complexity and optimized field primitives. Gajbhiye et al (2012) reviewed Elliptic Curve cryptography security, focusing on the performance attributes of the elliptic curve. They suggested that the Koblitz offers superior security features among the various curves and demonstrated how Koblitz curves can efficiently compute ord (p) on any curve P, facilitating an efficient derivation process.…”
Section: Elliptic Curve Algorithmmentioning
confidence: 99%
“…They claim that the Montgomery Ladder-based ECSMA saves 50% space and 45% time, driven by the Karatsuba multiplier's sub-quadratic complexity and optimized field primitives. Gajbhiye et al (2012) reviewed Elliptic Curve cryptography security, focusing on the performance attributes of the elliptic curve. They suggested that the Koblitz offers superior security features among the various curves and demonstrated how Koblitz curves can efficiently compute ord (p) on any curve P, facilitating an efficient derivation process.…”
Section: Elliptic Curve Algorithmmentioning
confidence: 99%
“…Elliptic Curve Cryptography is a reliable and efficient public key cryptographic technique that provides equivalent security as other public key cryptographic techniques but with smaller key size [10], [11]. Moreover, It is based on the discrete logarithm problem [12] which states that if K=nxG, then it is easy to derive K with given n and G, but tough to reveal n with given K and G. Thus with ECC, it will be tough for the blackhole attacker node to retrieve the private key from given secret key and public key.…”
Section: Why Ecc?mentioning
confidence: 99%
“…Both the symmetric and asymmetric schemes have trade-off between the security and its resources are constraint [4]. The main problem ofconventional Public key Cryptosystems is that the Key size has to be sufficiently large in order to meet the high level security requirement, resulting in lower speed and consumption of more bandwidth [5].The third technique i.e hybrid key technique which is the combination of symmetric and public key cryptography. It merges the advantages of both schemes.The feasibility of public-key cryptography (PKC) has been proven [6].…”
Section: Overview Of Cryptographymentioning
confidence: 99%